Universitas Terbuka (UT) Market Segmentation Analysis In South Sulawesi - Abdul Rahman rahim; Hasanuddin; Anfas; Syafiuddin (Institute of Computer Science (IOCS), 2022)
This study aims to identify market segments, analyze the target and positioning of Universitas Terbuka (UT) and determine strategies and implementations to increase the number of students. The method used was a survey method. Data collections were questionnaires and interviews. The collected data were analyzed using descriptive analysis. The results show that enrolling at Universitas Terbuka has so far been dominated by applicants aged 21-50 years, generally women, mostly working in the informal sector, earning less than 5 million Indonesian rupiahs, and coming from all regions. Generally, they feel they know UT but know more when they have become UT students. However, around 23.7 percent know UT from 2-5 years before becoming UT students. The media with the biggest contribution to introducing UT are friends, family, and leaders where they work, another part of them stated that the information is from those who studied at UT. Furthermore, only 14 percent stated that they knew UT from TV or social media. Then, the main consideration in deciding to register at UT was the cost factor. They consider the cost of tuition at UT is cheap, although some still think that tuition fees are still expensive but still affordable. After becoming UT students, they admit that communication with all components that play a role in learning at UT goes well. Further, argue that it is necessary if UT always informs/establishes cooperation with various parties, especially government and private institutions, especially in the regions.